Análise energética de um sistema fotovoltaico/térmico e sua integração a uma unidade de poligeração - Lima, Álvaro Augusto Soares (2021)
This thesis aims to study the behavior of the photovoltaic/thermal (PV/T) system and its integration in a polygeneration unit formed by a motor-generator group, absorption chiller and recovery boiler. The PV/T system was studied through a parametric analysis, where the influence of the slope, orientation and water flow of the collector on the electrical power, thermal power, temperature distribution and efficiency of the system was evaluated. For the polygeneration model, the capacity of the system to meet the demand for electricity, steam and cold in an ice cream factory was analyzed. The analysis for the PV/T system was performed numerically using MATLAB, where the radiation model and the finite difference method were implemented. For the polygeneration model, the EES (Engineering Equation Solver) was adopted, where the equations for the conservation of mass, energy and species were modeled. Among the main results obtained, it can be highlighted a higher electrical power generation by the PV/T system in up to 12.35% for the system inclined at 7.17º and oriented to the north over to the other cases. As for the polygeneration system, it is worth highlighting the 2.5% increase in electricity production and 4.41% increase in steam production when the PV/T module is coupled.